Yoga as a method of symptom management in multiple sclerosis - Frank, Rachael; Larimore, Jennifer (Frontiers in Neuroscience, 2015)
Multiple Sclerosis (MS) is an immune-mediated process in which the body’s immune system damages myelin in the central nervous system. The onset of this disorder typically occurs in young adults, and it is more common among women. Currently, there is no cure and the long-term disease progression makes symptomatic management critical for maintaining quality of life. Several pharmacotherapeutic agents are approved for treatment, but many patients seek complementary and alternative interventions. Reviews have been conducted regarding broad topics such as mindfulness-based interventions for people diagnosed with MS and the impact of yoga on a range of neurological disorders. The objective of the present review is to examine the potential benefits of yoga for individuals with MS and address its use in managing symptoms including pain, mental health, fatigue, spasticity, balance, bladder control, and sexual function.